Interventions for vector-borne diseases focused on housing and hygiene in urban areas: a scoping review - Stéphanie Degroote; Kate Zinszer; Valéry Ridde (BMC, 2018)
Abstract Background Over half the world's human populations are currently at risk from vector-borne diseases (VBDs), and the heaviest burden is borne by the world's poorest people, communities, and countries. The aim of this study was to conduct a review on VBD interventions relevant to housing and hygiene (including sanitation and waste management) in urban areas. Main body We conducted a scoping review, which involved systematically searching peer-reviewed and grey literature published between 2000 and 2016 using five scientific databases and one database for grey literature. Different data extraction tools were used for data coding and extraction. We assessed the quality of each study using the Mixed Methods Appraisal Tool and extracted descriptive characteristics and data about implementation process and transferability from all studies using the Template for Intervention Description and Replication and ASTAIRE (a tool for analyzing the transferability of health promotion interventions) tools. We reviewed 44 studies. Overall, the studies were judged to be of high risk for bias. Our results suggest multifaceted interventions, particularly community-based interventions, have the potential to achieve wider and more sustained effects than do standard vertical single-component programs. The evaluations of multifaceted interventions tend to include integrated evaluations, using not only entomological indicators but also acceptability and sustainability indicators. Conclusions This review highlighted the important need for higher quality research in VBDs and improved and standardized reporting of interventions. Significant research gaps were found regarding qualitative research and implementation research, and results highlighted the need for more interventions focus on sanitation and hygiene practices.